The unique chemistry in the envelopes of massive stars - Ziurys, Lucy M. (Frontiers in Astronomy and Space Sciences, 2025)
The envelopes of evolved massive stars (M ∼9–40 M⊙) on the Red Supergiant (RSG) Branch offer a unique situation to examine extreme circumstellar chemistry. Unlike their counterparts on the Asymptotic Giant Branch (AGB), these envelopes undergo energetic and highly-directional mass loss events, which distort a mostly spherical stellar wind. The envelope is subject to isolated shocks, grain destruction and dredge-up, all which generate a very complex chemical environment. Molecule formation involves thermodynamic equilibrium, localized shock heating, and varied elemental enrichment, frequently on timescales of a few hundred years. In this energized, oxygen-rich material, refractory oxides are synthesized, including AlO, PO, AlOH, TiO and VO, as well as metal halides (NaCl, AlCl, KCl, and AlF), but often with varying spatial distributions. High resolution imaging of molecular emission in the classic RSG, VY Canis Majoris (VY CMa) has given chemical and physical insight into these unique objects, but further studies are clearly needed.